(untitled) (International Seven Journal of Multidisciplinary, 2022)
Three-dimensional architectural visualization has become a critical tool not only for presenting projects but also for influencing client decision-making. This study presents a comparative analysis of visual strategies employed in popular (affordable) versus high-end architectural projects, emphasizing how rendering techniques, composition, lighting, and post-production can be optimized to persuade distinct client segments. For popular housing, visuals prioritize clarity, functional cues, and risk reduction, enhancing understanding and trust through realistic everyday contexts and measurable metrics. In contrast, high-end projects leverage aspirational imagery, material authenticity, and narrative-driven compositions to engage clients emotionally and symbolically, promoting identity projection and desire. The findings highlight that effective architectural visualization requires tailoring visual strategies to the decision heuristics of the target audience, demonstrating that the persuasive power of 3D models depends not only on technical realism but also on the strategic communication of value and experience.